Self-help literature in socialization processes: Implications for teacher education and teaching professionalization - Fiorio, Mariana [UNESP]; Penteado, Regina Zanella [UNESP]; Arnosti, Rebeca Possobom [UNESP]; Neto, Samuel de Souza [UNESP] (Mary Lou Fulton Teacher College, 2024)
This article aims to analyze the experiences of future teachers with self-help literature (SHL) in teaching socialization. The qualitative and descriptive research involved 16 future teachers from the first to fourth year of a pedagogy course at a public university in São Paulo state. Discursive data were obtained through semi-structured interviews. The content analysis yielded categories that address issues related to SHL (access, mobilizing consumption demands, assigned meanings and contributions), considering the instances of primary socialization (family and schooling) and secondary socialization (university education). Highlights in the results: a) the human and relational dimension of teaching; b) student suffering, illness and discomfort; and c) the paradox of SHL offering short-term answers and solutions and, at the same time, limited forms of enlightenment, comprehension and understanding. In processes that align with professional development and the construction of teaching as a profession, the implications of SHL presence in teacher education involves considering limitations (semi-formation and the production of precariousness and misery) and possibilities (human and emancipatory education).
Literatura de autoayuda en procesos de socialización: Implicaciones para la formación y profesionalización docente
A Literatura de Autoajuda em Processos de Socialização: Implicações na Formação e na Profissionalização Docente
Keywords: pedagogy; self-help literature; socialization; teacher education; teacher well being